Pemanfaatan Media Publikasi Dalam Promosi Potensi Desa Di Ponorogo - Ayub Dwi Anggoro; Happy Susanto; Rizal Arifin; Oki Cahyo Nugroho; Eli Purwati; Irvan Nur Ridho (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The study with the title of a publication's media use in the promotion of a potential village in Ponorogo is aimed at identifying villages that are already using the publications and their application. The study uses library research, which involves research done by gathering information and data with the help of such materials as reference books, similar research, articles, notes and journals that deal with problems that will be solved. The population of this research is a village located in the Ponorogo district. The sample to be used is the village of Grogol, the village of Gundik, village of Karangan, village of Plunturan, village of Tonatan, village of Bringinan and village of Paringan. In the media use of publications, villages have already obtained socialization about information technology and communication. With socialization and practice, communities feel an increased understanding and skill in understanding the importance of using social media to improve village competitiveness. The use of media for village publications in Ponorogo remains to be maximum. There are still authorities and villagers who are unfamiliar with the Internet and technology. It is known that within the management of the media, there must be a need for human resources that understand the internet and technology.